Cultural Resistance Form of Tattoo as a Pop Culture in Jakarta - Teguh Hidayatul Rachmad; Kho Gerson Ralph Manuel (Jurnal Spektrum Komunikasi, 2022)
Within the eastern culture, Tattoo has various meanings. They were resulting in range of perceptions towards people with a tattoo on their body. This study aimed to explore the alteration of meaning towards Tattoo in Indonesian urban society. This study use ethnography aimed to explain reasons and elements behind a cultural phenomenon. Liminal situation theory, used as an analysis tool to explore Tattoo cultural resistance. The results show that various meanings and symbols are attached to a tattoo in the act of self-expression method. Further results show that Tattoo also has a function as a cultural preservation method, notably Indonesian culture, in the form of a sub-culture. Tattoos are not only popular and owned by one group of people within a society but in a huge range of ages and social hierarchies.